Scientific rationality and evaluative perception on indigenous plant protection practices on coconut (Cocos nucifera L.) - Husain, A. Sakeer; Sundaramari, M. (Journal of Plantation Crops, 2011)
This study documented 116 Indigenous Plant Protection Practices (IPPPs) on coconut in Kerala where in more practices were registered in the technology dimension of 'control of rhinoceros beetle' (23.28 %), followed by general plant protection measures (11.21 %) and control techniques of termites (10.34 %). Of the practices, 75 % belonged to pest management practices, while only 25 % were related to disease management. Out of the 116 practices, 47 were selected for further analysis. Of these 47 practices, 39 practices (82.98 %) were found rational; the underlying scientific rationales/operational principles were also analysed in the study, which revealed the strong scientific base of these practices. However, only nine practices out of the 47 practices were known to more than 50 % of the farmers, reflecting the low level of knowledge of farmers on IPPPs on coconut. Similar was the situation, in the case of adoption. Further, out of the 47 selected practices, eight practices were analysed for their perceived effectiveness and found that six practices (75 %) were found rational and effective. Unraveling the indigenous technical knowledge should therefore be a research priority which in turn would enrich our agricultural technology.